(untitled) (International Journal of Current Research in Physiology and Pharmacology, 2023)
Substance use disorders are a major health problem worldwide. Substance use is a chronic disorder associated with significant mortality and morbidity. These diseases also cause significant healthcare utilization and medical costs. Substance use disorders occur when the use of alcohol, prescription drugs, or illegal drugs causes problems in his life and daily activities. Substance use disorders encompass a variety of behaviors, including but not limited to addiction, overuse, and behaviors caused by dangerous substances. Diagnosis is based on behavioral criteria, which include the inability to control substance use, dysfunction at school, home, or work, interpersonal problems caused or worsened by substance use, and risky or hazardous use of the substances. The first step in treating substance use disorders is to stop using the substance. In extreme cases of physical dependence, detoxification is necessary to help with withdrawal symptoms. Creating a supportive environment and eliminating triggers for substance abuse are essential to overcoming a substance abuse disorder. Treatment in management can be outpatient or inpatient, depending on the severity of the problem. Depending on the person’s condition, a doctor may suggest individual counseling from a psychologist, psychiatrist, or addiction counselor. Family counseling is often important. A doctor may also recommend specific rehabilitation and/or treatment programs; Self-help groups for children and families with addiction problems are often very helpful. In this article, we would like to briefly review substance use disorders and treatment modalities that are available to treat them. Keywords: Substance use disorder, Alcohol, Cannabis.